2005
DOI: 10.1007/s10826-005-1113-0
|View full text |Cite
|
Sign up to set email alerts
|

Strength-Based Assessment of Rural African American Early Adolescents: Characteristics of Students in High and Low Groups on the Behavioral and Emotional Rating Scale

Abstract: Early adolescents' strengths were examined in relation to factors that are associated with developmental risk or resilience in two rural low-income southern communities. The sample was comprised 279 students (101 boys, 178 girls), all of whom were African American and reflected the public school attendance of this community. Parent reports on the Behavioral and Emotional Rating Scale (BERS) were used to assess strengths. BERS scores were examined in relation to academic, behavioral, and social characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…This finding confirms those of previous studies that showed that strengths in some domains are related to positive outcomes in other settings (Farmer et al, 2005;Lyons et al, 2000). As well, the significant correlations observed between behaviour ratings, peer relationships, and academic achievement are supported by a line of research that has examined influences on academic achievement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding confirms those of previous studies that showed that strengths in some domains are related to positive outcomes in other settings (Farmer et al, 2005;Lyons et al, 2000). As well, the significant correlations observed between behaviour ratings, peer relationships, and academic achievement are supported by a line of research that has examined influences on academic achievement.…”
Section: Discussionsupporting
confidence: 90%
“…Assumed outcomes of a strengths-based approach are improvements in school engagement, achievement, pro-social classroom behaviour, and reductions in bullying and victimization (Anderson, Rawana, Brownlee, & Whitley, 2009;Donnon, Hammond, & Charles, 2003;Katz & McCluskey, 2003). Recent research has supported the relationships between these constructs (Albrecht & Braaten, 2008;Anderson et al, 2009;Donnon & Hammond, 2007;Farmer et al, 2005).…”
Section: Résumé De L'articlementioning
confidence: 97%
“…The value of a strength-based perspective extends well beyond the assessment and support of child and youth with special educational needs and may also be relevant to the prevention of later accumulated problems (Farmer et al 2005). An instrument such as the BERS-2 that is based on strengths offers a positive starting point for teachers and parents for planning interventions aimed to prevent later problems of children.…”
Section: Discussionmentioning
confidence: 99%
“…Overall these measures possess very good psychometric properties and are useful in identifying children for services. While these scales are useful in identifying children in need of specialized services, they may not be helpful in describing the child or developing a child's support or treatment plan (Albrecht and Braaten 2008;Cox 2006;Drolet et al 2007;Farmer et al 2005;Furlong et al 2007;Rhee et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the convergent validity of the BERS-2 with primary grade students, 19 students with special education needs, 20 and kindergarten students 21 as well as Hispanic 22 and African-American youth 23 indicate that the instrument adequately operationalizes the construct of behavioral and emotional strengths. However, there are no known studies of internal consistency or convergent validity with residential group care populations.…”
Section: Behavioral and Emotional Rating Scalementioning
confidence: 99%